PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PT. GALATTA LESTARINDO - Rengga Wana Putra; Yulasmi Yulasmi; Susriyanti Susriyanti (Institut Administrasi dan Kesehatan Setih Setio, 2023)
The purpose of this study is to find out how much influence Brand Image and Brand Trust have on Purchasing Decisions with Consumer Satisfaction as Intervening Variabels at PT. Galatta Lestarindo. Methods of data analysis using a questionnaire, with a sample of 100 respondents. The data analysis method used is SEM. Based on the results of the study indicate that there is a positive and not significant effect between Brand Image on Consumer Satisfaction. There is a positive and significant influence between Brand Trust on Consumer Satisfaction. There is a positive and significant influence between Brand Image on Purchasing Decisions. There is a positive and significant influence between Brand Trust on Purchasing Decisions. There is a negative and significant influence between Consumer Satisfaction and Purchasing Decisions. Consumer Satisfaction does not mediate Brand Image on Purchasing Decisions. Consumer Satisfaction mediates Brand Trust on Purchasing Decisions. The variabel contribution of Brand Image and Brand Trust through Consumer Satisfaction is 37.9% while the remaining 62.1% is influenced by other variabels outside of this study. Based on the results of this study, it is expected that PT. Galatta Lestarindo can improve purchasing decisions by increasing Brand Image, Brand Trust and Consumer Satisfaction through each indicator.